SOSIALISASI SISTEM KEAMANAN BERBASIS INTERNET OF THINGS UMKM SIMBAR PALEMBANG - Deta Mediana, Arsia rini; Putra, Rian Rahmanda; Putra, Yulian Mirza; Putra, Dini Oktavia (Politeknik Negeri Sriwijaya, 2024)
The socialization and implementation of an internet of Things (IoT)- based security system at UMKM Simbar were carried out as a community service effort to disseminate university knowledge to the public. The background of this socialization activity stems from challenges faced by the partner, such as a lack of knowledge about IoT-based CCTV technology, uncertainty about its benefits, concerns about implementation, and the inability to optimize the system. Through a systematic approach, this activity encompassed several stages, including in-depth interviews to understand the needs and conditions of the partner, development of hardware and software for the IoT-based CCTV system, validation and testing of the device in various conditions, as well as intensive training for the partner on system usage and maintenance. The results of this activity indicate that the partner is able to understand and operate the system effectively, and the developed system has successfully improved security and operational efficiency within the partner’s business environment. Technical challenges encountered during the implementation, such as signal interference and sensor inaccuracies, were successfully addressed through appropriate technical solutions. Continuous evaluation and feedback from the partner also suggest that this system holds significant potential for broader adoption in small and medium-sized enterprises).